Pengaruh Profitabilitas Dan Leverage Terhadap Tax Avoidance - Putra, Agung Dwi; Sukiswo, Helmy Wahyu (JCA (Jurnal Cendekia Akuntansi), 2026)
The study aims to analyze how profitability and leverage influence tax avoidance among consumer non-cyclicals sector firms listed on the Indonesia Stock Exchange during the 2020–2024 period. Although this sector tends to exhibit relatively stable demand characteristics, indications of tax avoidance practices persist, making it relevant for further investigation. The research employs a causal quantitative approach using panel data regression analysis with a fixed effect model. By applying purposive sampling, 46 firms were selected as samples over a five-year observation period, resulting in a total of 230 observations. Profitability is proxied by Return on Assets, leverage by Debt to Asset Ratio, and tax avoidance by Cash Effective Tax Rate.The findings reveal that profitability and leverage affect tax avoidance both partially and simultaneously. Profitability has a negative effect on tax avoidance, indicating that higher profits are associated with increased tax burdens, thereby encouraging companies to minimize their tax payments. Similarly, leverage also shows a negative effect on tax avoidance, suggesting that firms with higher debt levels tend to utilize interest expenses as a tax shield to reduce taxable income. These results confirm that financial factors serve as key drivers influencing corporate behavior in engaging in tax avoidance practices. Keywords: Tax Avoidance, Profitability, Leverage